Brunski, Jan Jacek - Maur, Eduard - Pulaski, Michal - Valenta, Jaroslav (eds.): Mezi dvěma transformacemi. Československo a Polsko v letech 1947 (1948) - 1989.: MŠMT ČR + FF UK, Praha 2001. 237 s. ISBN 80-7308-01 5-X. - Nešpor, Zdeněk R. (Lidé města, 2003)
A review of the book by Jan Jacek Brunski, Eduard Maur, Michal Pulaski and Jaroslav Valenta.